2022
DOI: 10.1097/jnr.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Work–Family Conflict, Organizational Identification, and Professional Identification Among Chinese Nurses From a Resource Perspective

Abstract: Background:The miserable work conditions faced by many nurses around the world make them particularly prone to work-family conflict.Purpose: This study was designed to explain from a resource perspective how and when nurses experiencing work-family conflict are more likely to exhibit decreased levels of organizational identification and professional identification.Methods: A time-separation research design was used, and data were collected from 322 nurses in five hospitals in China. All of the hypotheses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Consequently, on issues related to gender, the findings of this study indicated no gender interaction that both genders experience work–family conflict and exhibit deviant behaviors in their respective work environment. Thus, from the available literature reviewed, the focus was on the female gender [ 8 , 11 ] among others. So, the finding of this study clearly showed that individuals’ genders inability to positively respond to mental exhaustion affects their mood in the home and in their workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, on issues related to gender, the findings of this study indicated no gender interaction that both genders experience work–family conflict and exhibit deviant behaviors in their respective work environment. Thus, from the available literature reviewed, the focus was on the female gender [ 8 , 11 ] among others. So, the finding of this study clearly showed that individuals’ genders inability to positively respond to mental exhaustion affects their mood in the home and in their workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Work-family conflict is defined according to Zakaria and Ismail [ 7 ] as a form of role conflict where the demands of work and family cannot be aligned in several ways. Yang et al [ 8 ] work-family conflicts occur when workplace role expectations are hindered by family responsibility. Other studies documented long working hours, role ambiguity and conflict, shift work, and high physical and psychological loads as possible sources of work–family conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Work-family conflict is perceived as specific conflict while performing roles, and it occurs when a person is distracted by many functions and becomes dissatisfied with their life (Gull et al, 2021). Others stated that work-family conflict occurs when the responsibilities at the workplace limit the fulfillment of individual obligations in the family and vice versa (Yang et al, 2022). Due to time and energy constraints, individuals cannot meet work and family requirements simultaneously.…”
Section: Work-family Conflictmentioning
confidence: 99%
“…arising in one of the roles. Factors such as role ambiguity, excessive workload, high physical and psychological work demands, frequent changes in the work environment, poor communication at the workplace, and work commitment are among the causes of Strain-based work–family conflict ( Yang et al, 2022 ) Behavior-based conflict is when the attitude specific to one role is not compatible with the attitude in the other role ( Ameti and Abaz, 2023 ). Behavior-based conflict occurs when the person cannot change his/her behaviors according to his/her roles.…”
Section: Introductionmentioning
confidence: 99%